Reciprocal translocations in cattle: frequency estimation - De Lorenzi, L.; Morando, P.; Planas, J.; Zannotti, M.; Molteni, L.; Parma, P. (Journal of animal breeding and genetics (1986), 2012)
Summary Chromosomal anomalies, like Robertsonian and reciprocal translocations, represent a big problem in cattle breeding as their presence induces, in the carrier subjects, a well‐documented fertility reduction. In cattle, reciprocal translocations (RCPs, a chromosome abnormality caused by an exchange of material between non‐homologous chromosomes) are considered rare as to date only 19 reciprocal translocations have been described. In cattle, it is common knowledge that the Robertsonian translocations represent the most common cytogenetic anomalies, and this is probably due to the existence of the endemic 1;29 Robertsonian translocation. However, these considerations are based on data obtained using techniques that are unable to identify all reciprocal translocations, and thus, their frequency is clearly underestimated. The purpose of this work is to provide a first realistic estimate of the impact of RCPs in the cattle population studied, trying to eliminate the factors that have caused an underestimation of their frequency so far. We performed this work using a mathematical as well as a simulation approach and, as biological data, we considered the cytogenetic results obtained in the last 15 years. The results obtained show that only 16% of reciprocal translocations can be detected using simple Giemsa techniques, and consequently, they could be present in no <0.14% of cattle subjects, a frequency five times higher than that shown by de novo Robertsonian translocations. This data is useful to open a debate about the need to introduce a more efficient method to identify RCP in cattle.